The Creativity Of Bedhaya Tunggal Jiwa Dance Creation In Grebeg Besar Ceremony In Demak Regency - Setyaningrum, Ikha Sulis; Cahyono, Agus; Triyanto, Triyanto (Universitas Negeri Semarang, 2019)
Bedhaya Tunggal Jiwa dance presents in the Islamic dimension and gives a new nuance to a ceremony in Demak regency. This dance has different package from Bedaya dance in Kraton because it is adjusted to area and Demak society. The purpose of this research is to analyse how the the creativity of the creation of Bedhaya Tunggal Jiwa dance in Demak Regency. The method used was qualitative with ethnochoreology, Anthropology of Arts, and Sociology of Arts. The research data was collected by the technique of observation, interview, and document study. The technique of data validity used source triangulation. The data analysis technique that was used data reduction, data presentation and conclusion was done by describing the dance, understanding the the performance components, and doing interpretation. The results of the research were that the creator made a work through some steps, they are exploration, improvisation, evaluation, composition, and supported by creative factors, such as environment, facilities, skills, identity, originality, and appreciation.